Validity of SIPENA: An AI-Integrated Web-Based Application for Mathematics Teachers Learning Administration - Asri Wahyuni; Yugi Hilmi (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2026)
The rapid advancement of digital technology requires mathematics teachers to have strong pedagogical competence in designing and managing learning materials effectively. However, many teachers still face challenges in preparing comprehensive learning documents, such as Annual Programs (Prota), Semester Programs (Promes), teaching modules integrated with student worksheets (LKPD), assessment instruments, reflections, document covers, and class administration records. This study aimed to develop and assess the validity of SIPENA (Sistem Perangkat Pembelajaran/Learning Administration System), an AI-integrated web-based application that automatically generates complete learning documents for mathematics teachers. The development followed the 4D model (Define, Design, Develop, and Disseminate), limited to the first three stages. Expert validation was conducted by a media expert and a content expert using Likert-scale instruments. The results showed a media validity 86.36% and content validity of 96.84%, both were categorized as Very Valid. Usability was awarded the highest score by media experts (96.00%), while content experts confirmed that their product matched Merdeka Curriculum perfectly (100.00%). This study finally provides a valuable contribution to the field of AI-based educational technology in mathematics education context in Indonesia by showing that SIPENA can serve as both a valid and feasible platform to use for supporting mathematics teachers pedagogical competences in the digital era. This study was intentionally limited to evaluating the validity aspect of SIPENA development, while its effectiveness and effect size will be explored in a subsequent publication.